Kajian Terhadap Putusan MK Nomor 168/PUU-XXI/2023: Analisis Pergeseran Paradigma Ketenagakerjaan Terkait Pemutusan Hubungan Kerja (PHK) - Mayzura Kamila Sukma; Kezia Ananda Restu; Gracia Tirta Imanuella; Cindy Valentina (JURNAL ILMIAH NUSANTARA, 2025)
This study aims to analyze the content and implications of the Constitutional Court Decision No. 168/PUU-XXI/2023 regarding the shift in the labor paradigm, particularly in the context of termination of employment (PHK) in Indonesia. The research method used is a normative juridical approach, focusing on relevant laws and the Constitutional Court decision as the main study materials. This decision marks a turning point in the development of labor law in Indonesia, where the Constitutional Court emphasizes the importance of balancing the protection of workers' rights and the flexibility granted to employers. The study finds that the decision reinforces stricter and more transparent procedures regarding PHK, while still providing space for employers to maintain flexibility in their business operations. This paradigm shift has significant implications for PHK practices, where worker protection is strengthened without obstructing necessary restructuring or business adjustments. The study also offers recommendations for strengthening regulations, improving implementation oversight, and providing more effective labor dispute resolution to ensure fair and sustainable application